Efl Secondary Students’ Experiences And Challenges In Hellotalk – Assisted Digital Storytelling In Learning Speaking - Anjani, Olivia; Suryaman, Maman; Pahlevi, Muhammad Reza (Peneliti.net, 2024)
This study aims to explore EFL secondary students’ experiences and challenges in HelloTalk-assisted digital storytelling in learning speaking. The students will practice using HelloTalk application to complete the digital storytelling activity. It includes choosing topic, gain information, composing script, and delivering stories. This study was using qualitative research with narrative inquiry. In order to uncover the student perspectives and insights in gaining a direct understanding of their experiences and challenges encountered during their practices, this study employed a semi-structured interview. The finding showed that students had positive response on HelloTalk-assisted digital storytelling in speaking classroom. It proven by the participants used HelloTalk actively to practice speaking through DST to trains their speaking practice, and scafold students’ confidence in target language. Nevertheless, there was students that found some difficulties related to their pronunciation and vocabulary. They still have the lack of vocabulary and low pronunciation that make them missed pronunciation when talking with language partners on HelloTalk app. Therefore, it can be said that the result of this study is EFL secondary students had positive response in HelloTalk-assisted digital storytelling in speaking classroom